Coarse‐grained and atomic resolution biomolecular docking with the ATTRACT approach. Issue 8 (13th December 2019) - Glashagen, Glenn; de Vries, Sjoerd; Uciechowska‐Kaczmarzyk, Urszula; Samsonov, Sergey A.; Murail, Samuel; Tuffery, Pierre; Zacharias, Martin
Abstract: The ATTRACT protein‐protein docking program has been employed to predict protein‐protein complex structures in CAPRI rounds 38‐45. For 11 out of 16 targets acceptable or better quality solutions have been submitted (~70%). It includes also several cases of peptide‐protein docking and the successful prediction of the geometry of carbohydrate‐protein interactions. The option of combining rigid body minimization and simultaneous optimization in collective degrees of freedom based on elastic network modes was employed and systematically evaluated. Application to a large benchmark set indicates a modest improvement in docking performance compared to rigid docking. Possible further improvements of the docking approach in particular at the scoring and the flexible refinement steps are discussed.